2011
DOI: 10.1177/0098628311401588
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Presentations

Abstract: Students often use PowerPoint for presentations. Pecha Kucha was introduced as an alternative type of PowerPoint presentation. Pecha Kucha is a fast-paced presentation style that forces students to focus on their message with automated, 20-second slides. Three studies, including a pilot, examined whether Pecha Kucha enhanced the quality of student presentations as compared to traditional PowerPoint presentations. In a pilot study, students chose their presentation style; those who selected Pecha Kucha had high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…According to A. M. Beyer (2011), the creative use of PowerPoint software has the potential to result in high student engagement on the side of both the presenter and the audience. In another study, it was found that pk is far more effective in terms of students' explaining skills than the traditional presentation format (Widyaningrum, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to A. M. Beyer (2011), the creative use of PowerPoint software has the potential to result in high student engagement on the side of both the presenter and the audience. In another study, it was found that pk is far more effective in terms of students' explaining skills than the traditional presentation format (Widyaningrum, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…From the need for storytelling to reach diverse audiences and sell ideas (Barker & Gower, 2010;Nishi, 2013), to the use of visual images to increase listeners' attention and recall of information (Kernbach, Eppler, & Bresciani, 2014), to the need to be concise in an age of shrinking attention spans (Evans, 2014), PechaKucha presentations can prepare students for those demands. Not only does research indicate that students' demonstrated communication competence is as strong or stronger in PechaKucha presentations as it is with traditional speaking styles (Beyer, 2011;Oliver & Kowalczyk, 2013), but students also view these presentations as "fun." Yet, PechaKucha presentations are not nearly as widespread as one might imagineperhaps because there is little pedagogical guidance available.…”
mentioning
confidence: 99%
“…While Pecha Kucha has been applied in educational contexts in odontology, 3 anthropology, 9 psychology, 10 business and marketing, 5 there are only a few examples in medical or nursing education 2 , 7 , 8 . During the course, our students put together 30 Pecha Kucha presentations in teams of four, on topics like complementary tests, examinations and special techniques in clinical medicine.…”
Section: To the Editormentioning
confidence: 99%